HARMONIZATION OF ISLAMIC LAW AND TRADITION IN MANDAR, INDONESIA: DISTRIBUTION OF INHERITANCE FROM A SOCIOLOGICAL PERSPECTIVE - Waode Mabrukah Azzahrah; Sri Astuti A. Samad; Inayatillah Djakfar; Nadirah (Malikussaleh Social and Political Reviews, 2026)
Indonesian Muslims divide their inheritance based on two legal systems: Islamic law and customary law (adat). This study examines the distribution of inheritance in the Mandar community, West Sulawesi, in the context of the harmonization of Islamic law and customary law in Banggae District, Majene Regency, from the perspective of legal sociology. The purpose of this research is to determine the distribution of inheritance based on customs. This research is a qualitative case study and a field study. The population consists of all residents of Banggae District. Data collection was carried out using observation, interview, and documentation techniques. The data were then analyzed using the sociological theory of Islamic law, editing, recording, and organizing techniques, and conclusions were drawn using inductive, deductive, and comparative analysis. This study concludes that the distribution of inheritance in the Mandar community, especially in Banggae, Majene, is carried out through Islamic law and customary law mechanisms, based on a peaceful agreement between the parties. In the sociology of law, the agreement with the deliberation mechanism to divide inheritance is a custom that has become a living law in society, so that there is harmonization between Islamic law and custom.